CaO‐Based CO2 Sorbents: From Fundamentals to the Development of New, Highly Effective Materials. Issue 7 (2nd July 2013) - Kierzkowska, Agnieszka M.; Pacciani, Roberta; Müller, Christoph R.
Abstract The enormous anthropogenic emission of the greenhouse gas CO2 is most likely the main reason for climate change. Considering the continuing and indeed growing utilisation of fossil fuels for electricity generation and transportation purposes, development and implementation of processes that avoid the associated emissions of CO2 are urgently needed. CO2 capture and storage, commonly termed CCS, would be a possible mid‐term solution to reduce the emissions of CO2 into the atmosphere. However, the costs associated with the currently available CO2 capture technology, that is, amine scrubbing, are prohibitively high, thus making the development of new CO2 sorbents a highly important research challenge. Indeed, CaO, readily obtained through the calcination of naturally occurring limestone, has been proposed as an alternative CO2 sorbent that could substantially reduce the costs of CO2 capture. However, one of the major drawbacks of using CaO derived from natural sources is its rapidly decreasing CO2 uptake capacity with repeated carbonation–calcination reactions. Here, we review the current understanding of fundamental aspects of the cyclic carbonation–calcination reactions of CaO such as its reversibility and kinetics. Subsequently, recent attempts to develop synthetic, CaO‐based sorbents that possess high and cyclically stable CO2 uptakes are presented.